Strategic management of local potential-based entrepreneurship through community empowerment on fish attractions Bendhung Lepen in Mrican Village Yogyakarta - Sudarti, S.; Triyono, Mochamad Bruri (Journal of Community Service and Empowerment, 2022)
This research was aimed (1) to know the internal environmental factors that affect the management of entrepreneurship strategies for fish tourism attraction Bendhung Lepen; (2) to know external environmental factors that affect the management of entrepreneurship strategies for fish tourism attraction Bendhung Lepen; and (3) to know the appropriate marketing system for the location of Bendhung Lepen fish attractions. The method used in this study was qualitative descriptive where data were obtained by means of interviews, observations, and documentation. The interview was conducted at random on visitors to fish attraction Bendhung Lepen, the community around the Gajah Wong river irrigation site, and the Bendhung Lepen Community. Field results were used for SWOT analysis consisting of IFAS tables, EFAS tables, IE matrices, and SWOT matrices. The results of the analysis on IFAS can be known that the score for internal factors of 3.43 which understands the internal condition of management of fish attraction management in Bendhung Lepen falls into the moderate category (average). This is because factors that have a high score were at high operational cost points. The results of the EFAS analysis showed a score of 3.28 which means the external condition of Bendhung Lepen fish attractions were in good condition, where the most dominant factor is the number of competitors was still small, balanced crop sales, and the density of the number of tourist attraction visitors.